PENGARUH IMPLEMENTASI E-LKPD BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN MATEMATIS SISWA - Hanny Cindy Prastica; Lina Rihatul Hilma; Ika Santia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model assisted by E-LKPD on the mathematical problem-solving ability of class X students on the material of arithmetic sequences and series at SMK Arrahmah Papar. The background of this study is based on the low interest and ability of students in solving mathematics problems, especially non-routine problems that require conceptual understanding and high-level thinking skills. The study used a quantitative approach with a pretest-posttest control group design. The research sample consisted of two randomly selected classes, namely the experimental class using the CTL model assisted by E-LKPD and the control class using the conventional learning model. The instruments used were in the form of a mathematical problem-solving ability test and media and material validation sheets. The results of data analysis showed that the average posttest score of students in the experimental class increased significantly compared to the control class. In the experimental class, the average score increased from 48.17 to 81.83, while in the control class it increased from 48.50 to 76.83. The Mann-Whitney statistical test and paired sample t-test showed a significance value of <0.05, which means there is a significant difference between the two classes. This finding indicates that the use of the CTL learning model assisted by E-LKPD is effective in improving students' mathematical problem-solving abilities. This study recommends that teachers apply the CTL model and utilize interactive E-LKPD media as an innovative learning strategy to improve student engagement and understanding in mathematics lessons.